PENGARUH DOSIS PETROGANIK DAN PUPUK HAYATI PETROBIO TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN CABAI MERAH (Capsicum annum L.) VARIETAS GADA F1 - Yepi Nopiandi; M. Darul Anwar (Jurnal Ilmiah Hijau Cendekia, 2017)
The importance of this research is to know the effect of the dose of “Petroganik” and bio-fertilizer to the growth of Chilli Red varieties Gada F1. The research was conducted on UD land. Rejo Tani, Ds. Kuniran, Kec. Baron, Kab. Nganjuk from January to April 2017. This study used a randomized block design (RAK) which was repeated three times and consisted of two factors. The first factor is the dose of petroganic fertilizer (P) with three levels and the second factor is the dosePetrobio (B) consist three levels. The results of this study were: 1) a combination of treatment of “Petroganik” fertilizer and Petrobio bio-fertilizer did not interaction on all parameters of observation on growth and production of Chilli Red (Capsicum annum L.) varietiesGada F1 ; 2) a combination of 2 ton / ha Petroganik fertilizer treatment and 60 kg / ha Petrobio bio fertilizer (P2B2) produced the best production in varieties Gada F1 (Capsicum annum L.)